2011
DOI: 10.1111/j.1462-2920.2011.02672.x
|View full text |Cite
|
Sign up to set email alerts
|

A periplasmic arsenite‐binding protein involved in regulating arsenite oxidation

Abstract: Arsenic (As) is the most common toxic element in the environment, ranking first on the Superfund List of Hazardous Substances. Microbial redox transformations are the principal drivers of As chemical speciation, which in turn dictates As mobility and toxicity. Consequently, in order to manage or remediate environmental As, land managers need to understand how and why microorganisms react to As. Studies have demonstrated a two-component signal transduction system comprised of AioS (sensor kinase) and AioR (resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
80
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 48 publications
2
80
0
1
Order By: Relevance
“…Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6,13,40); and, most recently, in anoxic photosynthesis (21,33 (28,31) indicated the role and importance of the sensor kinase AioS and its putative regulatory partner AioR (a bacterial enhancer binding protein), direct proof of these two proteins working together as part of a putative As III signal perception and transduction cascade was just recently provided by Sardiwal et al (54), who demonstrated the autophosphorylation of an AioS component and the AioS-specific phosphorylation of AioR. Recently, our work has expanded this regulatory model to now include a third component, AioX, which is a periplasmic As III binding protein that is also essential for aioBA expression (39 …”
mentioning
confidence: 98%
“…Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6,13,40); and, most recently, in anoxic photosynthesis (21,33 (28,31) indicated the role and importance of the sensor kinase AioS and its putative regulatory partner AioR (a bacterial enhancer binding protein), direct proof of these two proteins working together as part of a putative As III signal perception and transduction cascade was just recently provided by Sardiwal et al (54), who demonstrated the autophosphorylation of an AioS component and the AioS-specific phosphorylation of AioR. Recently, our work has expanded this regulatory model to now include a third component, AioX, which is a periplasmic As III binding protein that is also essential for aioBA expression (39 …”
mentioning
confidence: 98%
“…However, no or only one cysteine residue is present within the putative sensory domain of AioS. It was recently shown in A. tumefaciens that the protein that binds As(III) is, in fact, AioX, and it was proposed that this binding results in a conformational change of AioX, allowing its interaction with AioS (9).…”
mentioning
confidence: 99%
“…They must therefore delicately balance arsenic intracellular trafficking by controlling the expression of the genes involved in these mechanisms. Until now, only three regulators have been proposed to be involved in arsenic sensing: the ArsR and ArsD repressors and the three-component As(III) binding protein/sensor/regulator signal transduction system AioXSR (2,9,10). ArsR and ArsD act together to repress the basal and maximal levels of expression of the arsenical resistance ars operon of the Escherichia coli R773 plasmid.…”
mentioning
confidence: 99%
“…Complementation of an aioR::Tn5B22 mutant [As(III) oxidation minus] required the entire aio region, indicating genes in the aio operon are part of a common transcriptional unit (7). Thus far, it appears that there are at least two separate regulatory circuits controlling the expression of the aio operon: (i) a twocomponent signal transduction system, AioS and AioR, which recently has been shown to include AioX as a putative periplasmic signal receptor (8); and (ii) quorum sensing, which is normally involved in virulence of plants (2,5), is also involved in regulating As(III) oxidation in A. tumefaciens 5A (7).…”
mentioning
confidence: 99%
“…We report the draft genome of the arsenite [As(III)]-oxidizing A. tumefaciens strain 5A isolated from an As-enriched Typic Calciaquoll soil collected from an irrigated pasture in the Madison River Valley, MT (9). Complex regulation of arsenite oxidation, including As(III)-sensing, three-component signal transduction, and quorum sensing are involved (7,8). Prior to this genome report, only a single A. tumefaciens whole-genome sequence (strain C58) had been published (4).…”
mentioning
confidence: 99%